Analysis of Passenger Inspection during the Covid-19 Period at Zainuddin Abdul Madjid International Airport, Lombok, West Nusa Tenggara - Fitrah Ade Kurniawan; Desiana Rachmawati (CV. Rayyan Dwi Bharata, 2023)
Domestic travel by airplane during the COVID-19 pandemic requires several new things regulated in dynamic regulations that are adjusted to the conditions of the development of COVID-19 in the community and the control carried out by the government. Some new things that passengers must do during security checks by Aviation Security at SCP-1 and PSCP. The purpose of this study is to explain the passenger inspection procedures and obstacles faced by Avsec officers in conducting passenger checks on SCP-1 and PSCP during the Covid-19 pandemic at Zainuddin Abdul Madjid International Airport, Lombok, NTB. This study used descriptive qualitative methods, the informants interviewed consisted of 1 Supervisor and 1 Squad leader at SCP-1 and 1 Officer at PSCP, with data collection techniques using interview, observation and documentation methods. validity of qualitative data using triangulation method. The results found that passenger inspection procedures by Avsec officers at SCP-1 and PSCP underwent changes with several additional procedures. Additional procedures are implemented in accordance with the Circular Letter of the Minister of Transportation Number SE 82 of 2022, the Circular Letter regulates various matters related to health protocols, completeness of vaccination and matters related to safety from Covid-19 transmission during travel. The obstacles faced by Avsec officers when conducting passenger checks are related to compliance with health protocols, completeness of vaccinations, long queues so that the inspection time is longer than usual. The solution is in the form of adding emergency clinic facilities for passengers who need vaccination and maximizing services by existing Avsec officers.